2016
DOI: 10.1038/cddiscovery.2016.80
|View full text |Cite
|
Sign up to set email alerts
|

MICU1 may be a promising intervention target for gut-derived sepsis induced by intra-abdominal hypertension

Abstract: Intra-abdominal hypertension (IAH) is a common and serious complication in critically ill patients, for which there is no targeted therapy. IAH-induced dysfunction of intestinal barriers is closely associated with oxidative imbalances, which are considered to provide a pathophysiological basis for subsequent gut-derived sepsis. However, the upstream mechanism that produces oxidative damage during IAH remains unknown. It is not clear whether ‘mitochondrial Ca2+ uptake 1’ (MICU1, the key protein regulating the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…It has been demonstrated that FOXD1-dependent MICU1 expression regulates mitochondrial activity and cell differentiation [ 25 ]. Leng et al [ 26 ] revealed that MICU-related oxidation/antioxidation disequilibrium is strongly involved in intra-abdominal hypertension-induced damage to intestinal barriers. Another study revealed that MICU1 deficiency is associated with mitochondrial Ca 2+ uptake during aerobic metabolism impairment, muscle weakness and myofiber damage during physical activity [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that FOXD1-dependent MICU1 expression regulates mitochondrial activity and cell differentiation [ 25 ]. Leng et al [ 26 ] revealed that MICU-related oxidation/antioxidation disequilibrium is strongly involved in intra-abdominal hypertension-induced damage to intestinal barriers. Another study revealed that MICU1 deficiency is associated with mitochondrial Ca 2+ uptake during aerobic metabolism impairment, muscle weakness and myofiber damage during physical activity [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rats fasted for 12 h while water was free to access before operation. The IAH model was established according to the method previously described (Gong et al, 2011;Leng et al, 2016). In brief, rats were anesthetized with sodium pentobarbital 40 mg/kg by intraperitoneal injection.…”
Section: Intra-abdominal Hypertension Model Establishedmentioning
confidence: 99%
“…In a recent experimental study, Leng et al [37] indicated that mitochondrial Ca 2+ uptake 1 (MICU1)-related oxidation/antioxidation disequilibrium is strongly involved in IAH-induced damage to intestinal barriers. MICU1-targeted treatment may hold promise for preventing the progression of IAH to gut-derived sepsis.…”
Section: Recent Insightsmentioning
confidence: 99%